Revision of the described Nearctic species of the genus Tachydromia Meigen (Diptera: Hybotidae) - Shamshev, Igor V.; Grootaert, Patrick (Zootaxa, 2024)
The described Nearctic species of the genus Tachydromia Meigen, 1803 (Diptera: Hybotidae, Tachydromiinae) are revised. Seventeen described species are recognised. The following two new synonyms are proposed: Tachista lundstroemi Frey, 1913 (Eurasian species) = Tachydromia enecator Melander, 1902; Tachydromia hirtipes Melander, 1928 = Tachydromia schwarzii Coquillett, 1895. Five Eurasian species are recorded for the first time from North America (T. aemula (Loew), T. fuscinervis (Frey), T. incompleta (Becker), T. magadanica Shamshev, T. punctifera (Becker)) and two North American species for the first time from Eurasia (T. chelana Melander, T. monacha Melander). Nearly half of Tachydromia species recorded currently from North America have Holarctic distributions (53 %). However, many new species remain undescribed. Redescriptions, photos of the habitus and illustrations of male terminalia (when available), as well as known distributions and a key to species are included.